Prevalence of Nocturnal Enuresis Among Elementary School Students in Jalalabad, Afghanistan - Nasir, Ghazi Jamal Abdul; Shah, Sayed Ahmad (International Journal For Research In Biology & Pharmacy, 2019)
Prevalence of nocturnal enuresis among elementary school students in Jalalabad, Afghanistan. Background: nocturnal enuresis (bed wetting) refers to inability to control urination during sleep which is common issue in children above 5 years of age. This study aimed to determine the prevalence of nocturnal enuresis in elementary schools of Jalalabad. Methods: This cross sectional study conducted from 4th/April/2016 to 9th/April/2017 in elementary schools of Jalalabad city. 1400 questionnaire were distributed to students of two elementary schools (one governmental, one private). These questionnaire were answered by their parents. Results: from the data received 1339 questionnaire were analyzed. Mean age was 9.9 (SD=2,3), CI (9.8 – 10.5). Overall prevalence of nocturnal enuresis in elementary schools of Jalalabad was 19%. Means that out of 1339 students 254 had nocturnal enuresis. Additionally 15/6% had UTI and 34% had both UTI and enuresis. Showing UTI as potential cause of enuresis. In relation to gender the prevalence of nocturnal enuresis in the boys (22.4%) was higher compared with that in the girls (14%). P<0.05 Conclusion: Our results with enuresis prevalence were comparable to other epidemiological studies from various countries. We found that afghan families do not pay sufficient attention to their enuretic children.